2019
DOI: 10.1186/s12302-019-0210-4
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of soil contamination by cypermethrin residues using phytoremediation with Plantago major and some surfactants

Abstract: Background: Surfactant-enhanced phytoremediation is an eco-friendly treatment for reducing soil contamination. Cypermethrin (CYP) is one of the most widely used pyrethroid insecticides against different pests, and its use causes soil contamination. The aim of this study was to investigate the removal of CYP from contaminated soil by Plantago major (PM) and some surfactants. For the first time, we documented the uptake and translocation of CYP from the soil and used some strategies to improve the effectiveness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 82 publications
0
21
0
Order By: Relevance
“…Phytoremediation is a technology which uses plants in the environment to immobilize, eliminate or process pollutants including pesticides (Matsumoto et al, 2009;Aioub et al, 2019). Based on this study, although PM and tomato accumulated signi cant amounts of CYP in their tissues.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Phytoremediation is a technology which uses plants in the environment to immobilize, eliminate or process pollutants including pesticides (Matsumoto et al, 2009;Aioub et al, 2019). Based on this study, although PM and tomato accumulated signi cant amounts of CYP in their tissues.…”
Section: Discussionmentioning
confidence: 83%
“…Plantago major (PM) called plantain plant is a well-known perennial herb that grows in many areas such as the meadowland, roadsides, elds developed, canal water and waste zones (Sharifa et al, 2008). The broad surface area of their brous roots and their phytoremediation capability has used PM as a curative plant (Romeh 2010;Romeh 2016;Aioub et al, 2019). Chekol et al, (2002) mentioned that intense soil penetration has to do with a wide brous roots surface.…”
Section: Introductionmentioning
confidence: 99%
“…Anwar et al (2011) investigated residues (0.031 mg kg −1 ) in peach fruits in Nawab Shah, Sindh, and Shah et al (2011) reported concentration of CYP (1.86 mg kg −1 ) in alkaline soils. Various organic and inorganic amendments were applied to biodegrade different group’s pesticides for various fruits crops ( Mohapatra and Phale, 2021 , Aioub et al, 2019 , Mukherjee, 2009 ). Different studies showed that combined application of organic and inorganic amendments were effective to reduce residual effect of CYP.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study showed that a surfactant increased the mobility of metribuzin in soil [28]. Thus, surfactants can be used to remove residual pesticides in soil by solubilizing sorbed pesticides [29]. The increased mobility of pesticides in the presence of surfactants can lead to increased absorption by plants in soil; however, our results show that the absorption in the presence of Triton X-100 was not significantly different from that in the absence of Triton X-100 (i.e., watered with water).…”
Section: Effect Of Triton X-100 On Absorption Of Procymidone In Soil By Lettucementioning
confidence: 99%